Hole Quality Assessment Of Drilled Carbon Fiber Reinforced Polymer (Cfrp) Panel Using Various Drill Bit Design - Kamaruzaman, Muhammad Faris Shauqi (Universiti Sains Malaysia, 2021)
Drilling the carbon fiber reinforced polymer (CFRP) is crucial to maintain thrust force and hole quality even after several drilling processes. Excellent hole quality is necessary for the aerospace industry’s drilling process for highly abrasive carbon fiber reinforced polymer (CFRP). There have many twist drill that gives the good performance in hole quality but during in this research three different of custom twist drill bit geometries in term of helix angle, primary clearance, point angle and chisel angle, which are polycrystalline diamond (PCD), tapered web, burnishing drill bit was used in the drilling of the CFRP panel. Those drill bits for the main body of the drill bit were made up of powder tungsten carbide that undergoes the sintering process, and for PCD design the cutting tool is made up of PCD while for tapered web and burnishing is still used tungsten carbide. The main objective of this research is to optimize the drilling parameter that gave the minimum of thrust force, minimum of hole surface roughness, minimum of hole diameter error, and a minimum of hole delamination for various drill bit designs for the hole drilling using spindle speed (range of 1500 rev/min to 4500 rev/min) and feed rate (range of 0.05 mm/rev to 0.1 mm/rev) respectively. The result was subsequently evaluated using the analysis of variance (ANOVA) to determine the various custom drill bit design in terms of different drilling parameters on the maximum thrust force and the hole integrity of drilled hole. The finding indicates that the R1(1500 rev/min and 0.05 mm/rev) for PCD, R2 (1500 rev/min and 0.075 mm/rev) for tapered web, and R3(1500 rev/min and 0.1 mm/rev) for burnishing drill bit design gave the best drilling parameter by generating the least thrust force. least of hole surface roughness, least hole diameter error value, and also least hole delamination factor. In conclusion, the thrust force is directly proportional to the hole surface roughness, hole diameter, and hole delamination factor when drilling a CFRP material in a single shot operation. The higher of drilling parameter of every single drill bit designs produced higher value for all responses that prove that it design of twist drill need to improvise in term of geometries to give the good performances for all try.